2n + 6 = 3 + n ; this is an equation of one variable {n}. It can be solved for a value of n:
subtract n fro both sides: 2n + 6 - n = 3 + n - n ---> n + 6 = 3.
subtract 6 from both sides: n + 6 - 6 = 3 - 6 ---> n = -3. You should then substitute n=-3 back into the original to check your work.
2(-3) + 6 = -6 + 6 = 0 | 3 + (-3) = 0, so it checks out.
Chat with our AI personalities
2n plus 7 equals 19 2n equals 12 n equals 6
Given that 2n = 6 + n, subtract n from each side and n = 6
6=(1-2n)+5 6-5=(1-2n)+5-5 1=1-2n 1-1=1-1-2n 0=-2n 0/-2=-2n/-2 0=n
(4n + 1)*(2n + 6) = 8n2 + 26n + 6
(2n - 3)(n - 6)